The Dynamics of Competence-Equating Policy Implementation in the ASEAN Economic Community Era: A Study on the Construction Sector Workers - Soemartono, Triyuni (International Journal on Advanced Science, Engineering and Information Technology, 2016)
In terms of the ASEAN Economic Community, to facilitate the liberalization of trade in services in the ASEAN region, ASEAN Mutual Recognition Arrangement (MRA) have been agreed,  within which the construction sector, particularly the construction workers (engineers and architects), has become a sector that was agreed to be opened. This requires a quick equating of competence so that Indonesia is ready to compete. This study aims to look at issues emerging in the implementation of competence-equating policy in Indonesia, especially in order to face the AEC. It uses a qualitative approach. The results show that the dynamics of problems obstructing the implementation of the policy are among others i.e. Firstly, certification of Competence is not considered important in a career, which many workers consider that the need for certification is only to meet the required status, they do not consider it as their own personal need, although competence certification is an indicator of career progress. Secondly, there is a gap between academic world and the working world, which many consider that education and training are still not capable to fulfil the basic needs of construction workers with particular capability to work in the field. Thirdly, The role of Government and the Association in Implementing the policy on the field has been ineffective which the role of government to implement these regulations, including in socialization and competence training is still considered insufficient and associations are considered not actively voicing the importance of competence.